Influence of dike slope on the development of infiltration water and erosion processes during overtopping tests - Hassan, Marwan; Ismail, Mohd Ashraf (International Journal of Engineering and Technology, 2018)
The usage of dikes embankments has a great influence on the development of hydraulic engineering. It increases the suitability of water resources for humanity needs. Different Geotechnical and hydraulics powers affect on the stability of dike construction through transition of water flow in the upstream slope. The development of erosion process inside dike construction occurred as a result of an overtopping water flow cross above the dike crest. The dike erosion initiates breach channel inside dike and later widened into upstream and downstream slopes. In this study, a 2D and 3D vertical and horizontal erosions test is constructed in Hydraulic Geotechnical laboratories at the Universiti Sains Malaysia to observe the evolution of the breach channel during spatial overtopping failure. Two constant dike slopes of (1V:3H) and (1V:2.5H) for both upstream and downstream slopes are used as a parametric test during overtopping tests. The vertical and horizontal distributions of water levels are also highlighted prior to overtopping failure. The results indicate that the vertical and horizontal erosion widen the dike breach for slope of 1V:2.5H faster than those for 1V:3H while the spread of water infiltration in horizontal and vertical levels are higher for latter slope than for previous one.